Modeliranje električkih karakteristika fotonaponske amorfno-nanokristalične silicijske ćelije : doktorski rad - Tudić, Vladimir; Tešnjak, Sejid; Gracin, Davor (Zagreb, V. Tudić ; Fakultet elektrotehnike i računarstva, 2014)
SAŽETAK: U radu su opisana poluvodička svojstva silicija, hetero-spojevi silicija, istražen je foto-naponski efekt u intrinzičnom sloju, odnosno, generacija i rekombinacija slobodnih nosioca naboja. Opisane su fizikalne osnove jednoslojnih solarnih ćelija izrađenih od silicija, a predočen je amorfno-nanokristalinični silicij kao vrlo značajni kompozitni poluvodički materijal za izradu foto-naponskih ćelija visoke efikasnosti, takozvane solarne ćelije treće generacije. Navedene su strukturne, optičke i električne karakteristike tankih nc-Si:H filmova ustanovljenih različitim mjernim metodama i postupcima. Također, opisane su tehnologije izrade solarnih ćelija od tankih filmova silicija, koje se danas najviše koriste. Nadalje, u radu je dat opis temeljnih karakteristika jednoslojnih solarnih ćelija i postupaka karakterizacije ćelija kroz slojeve strukture, kao i njihovo modeliranje korištenjem računalnog simulacijskog programa AMPS-1D. Svi postavljeni modeli u ovom radu temelje se na jednoslojnoj pin strukturi, sa jednim ili više aktivnih slojeva, kako bi se rezultati dobiveni proračunom mogli usporediti s ostalim rezultatima objavljenim u relevantnoj literaturi. Korišteni su modeli pin ćelije s jednim homogenim aktivnim slojem kao i modeli s višeslojnim homogenim aktivnim slojevima, koji, zapravo, opisuju nehomogenu strukturu u slučaju postojanja aktivnih slojeva većih debljina. Kroz ukupno osam grupa simulacija opisane su izlazne električne karakteristike modeliranih struktura osvijetljenih solarnih ćelija čiji su aktivni slojevi izrađeni od amorfnog silicija, amorfno-nanokristaliničnog silicija i nanokristaliničnog/mikro-kristaliničnog silicija. Promjenom optičkih i električnih parametara slojeva, ulaznih i graničnih uvjeta, kao i mijenjanjem količine primjesa i nečistoća u slojevima ćelija, izračunima su dobivene matrice podataka električnih parametara solarne ćelije. Prije svega, razmotrene su strujno-naponske karakteristike modeliranih struktura, faktor popunjenosti i efikasnost solarne ćelije. Podaci su opisani i predočeni grafički, a u zaključim razmatranjima je dana je analiza rezultata simulacija i proračuna. Predmetnim znanstvenim radom ostvarene su sve postavke hipoteze uključivo i očekivani izvorni znanstveni doprinos. - KLJUČNE RIJEČI: silicij, foto-naponski efekt, generacija, rekombinacija, amorfni, nanokristalinični, AMPS-1D, faktor popunjenosti, efikasnost
EXTENDED ABSTRACT: The composite a-nc-Si:H thin films have been the subject of intense research for variety of applications due to their unique optical and electrical properties. Out of the many applications silicon thin films are used in thin layer transistors, tunable photo-diodes, and potential applications of composite silicon thin films are in third generation photovoltaic. First benefit of using a-nc-Si:H concerning optical properties. The optical gap of amorphousnano- crystalline thin film materials can be adjusted in wide range with variation of size distribution of individual crystal sizes and the crystalline to amorphous fraction. The nanocrystals remain as individual in amorphous matrix enabling quantum size effects related to small dimensions of crystals. Evaluation of the optical properties and structural analysis of thin silicon samples showed that the spectral distribution of the absorption coefficient, in a wide range of crystal to amorphous fractions, can be maintained close to pure amorphous silicon in the visible part of the spectrum and showed square dependence on the photon energy. The average optical gap was larger for smaller nano-crystals and a higher crystal fraction Xc just confirming the quantum size effects that correspond to quantum dots. The most efficient thin film production techniques were also described: PECVD - Plasmaenhanced chemical vapor deposition, HWCVD - Hot Wire Chemical Vapor Deposition and some others. Described samples of amorphous and amorphous-nano-crystalline thin films with a thickness between 100 and 200 nm were deposited by the PECVD method using radio frequency glow discharge in a capacitive coupled parallel plate reactor. The High-Resolution Electron Microscopy (HRTEM) measurements were performed in a JEOL JEM-2010F transmission and scanning electron microscope (TEM/STEM) for evaluation of structural properties in ordered domains. The size distribution was estimated after software image processing in the reciprocal space using Bragg masks in the Digital Micrographs software. The individual sizes of the nanocrystals were approximated as spheres with a circular projection. Silicon thin films samples described in this work in process of determination are used in composite form, which is primarily characterized by the crystal fraction Xc and crystal grains sizes. It is necessary to understand effects of complex micro structural features on the overall electrical properties of thin films. The resistance and capacitance of crystals grains and grain boundaries, which is frequency and temperature dependent are evaluated from IS spectra. This technique for determination of the starting values for the basic equivalent electrical circuit were used in the fitting procedure of experimental impedance data with simulated data in order to select most appropriate equivalent circuit. This technique enables to separate the real and imaginary component of the complex impedance and related parameters, and hence provides information of the structure-property relationship in the rated samples. In present work a semi conducting silicon properties, hetero-junctions and photo effect in intrinsic silicon thin films have also been studied, and optical generation and recombination of free carriers and transport model had been investigated. Better transport model HQD is suggested hence to structural nature of described and modelled composite silicon layers. Therefore, bases physical principles of simple silicon solar cells with accent to amorphousnanocrystalline layers as permissible composite material for high efficiency solar cells called third generation layers have been studied. Thin film characterisation techniques were characterised revealing structural, optical and electrical properties. In order to determine electrical characteristics a bases principles of pin structure solar cells have been carried out with one dimensional computer modelling programme AMPS-1D (Analysis of Microelectronic and Photonic Structures). Programme was primary used for parameter calculations of semiconductor devices, diodes, microelectronic and photonic structures. All suggested solar cell models are based to simple pin structure in order to compare simulation results with others in references. Computer modelling programme allows solar cell parameter calculations and structure design simulations. By varying significant ranges of solar cells parameters such as: illumination spectra, photon flux, absorption coefficient, boundary conditions, front and back contact parameter, general silicon layer parameters as doping and free carrier concentrations, mobility, gap state defect distribution, I-V characteristic, fill factor (FF), and efficiency (h) of solar cell can be determinate. In this work eight (8) simulation groups are carried out with intrinsic layers of amorphous (a-Si:H), amorphous-nano-crystalline (a-nc-Si:H) and micro-crystalline (μcSi:H) materials. Suggested model performed calculations in homogenous absorber layer, two-phase and absorber-multilayer solar cell structures. Solar cell with homogenous absorber layer showed efficiency of almost 14% at thickness of 1μm. Calculated efficiency of absorber-multilayer solar cell structure of thickness 500 nm in final simulation reached 12,3%. All calculated solar cells data of all modelled structures were graphically presented and discussed. - KEYWORDS: silicon, photo effect, optical generation, recombination, amorphous, nano-crystalline, AMPS-1D, fill factor, efficiency
Na spor. nasl. str. naslov na eng. jeziku: Modelling of electric characteristics of the photovoltaic amorphous-nanocrystalline silicon cell : doctoral thesis
Bibliografija: str. 223 - 242. - Sažetak na eng. i hrv. jeziku. - Životopis [uključuje i popis radova autora]